Synthesis and Biological Activity of N-(arylsulfonyl) Valine Hydrazones and Assistance of NMR Spectroscopy for Definitive 3D Structure - TATAR, ESRA; KÜÇÜKGÜZEL, İLKAY; BİNGÖL ÖZAKPINAR, ÖZLEM; ŞENKARDEŞ, SEVİL; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ; ŞEKERLER, TURGUT (BENTHAM SCIENCE PUBL LTD, 2019)
Background: Hydrazide-hydrazones constitute an important class of compounds for new drug development. In this study, a series of 39 new acylhydrazones (3-41), derived from (2S)-3-methyl-2-[[( 4-methylphenyl)sulfonyl]amino]butanoic acid hydrazide were synthesized with further aim to achieve biologically active acylhydrazones carrying an amino acid side chain. Methods: Compounds 3-41 were synthesized by microwave-assisted method. All synthesized compounds have been tested for their anti-HIV activity compound 21 was subjected to a new set of 2D-NMR analysis for the characterization of the isomers in solution and determination of its 3D structure. Results: The IC50 values for compounds 2-40 were found between >125-10.90 mu g/ml against HIV-1( IIIB) and HIV-2(ROD) strains in MT-4 cells. Compounds 3, 6, 10, 12, 23, 24, 27, 32, and 37 with CC50 values between 10.90-14.50 mu g/ml were selected to evaluate for their antileukemia activity. IC50 values for these mentioned compounds were found as >100 mu M on human chronic myelogenous leukemia, K562 cell line. Conclusion: Some compounds with IC50 values between 10.90-14.50 mu g/ml will be of benefit in the development of novel leads.
Keywords: Acylhydrazones; anti-HIV activity; antileukemia activity; 2D-NMR spectroscopy; 3D structure; L-valine; microwave assisted synthesis; ACYLHYDRAZONE DERIVATIVES; ANTITUBERCULAR ACTIVITY; HCK INHIBITORS; CANCER; IDENTIFICATION; ANTICANCER; APOPTOSIS; REPLICATION